2009
DOI: 10.1634/theoncologist.2009-0002
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Therapy in Hodgkin’s Lymphoma

Abstract: 1. Appraise the most important properties of a salvage chemotherapy regimen and name at least three effective regimens.2. Evaluate poor-risk clinical features pre-HDCT/ASCT that reduce the chance for cure and design a more effective alternative transplant approach.3. Hypothesize the reasons for the effectiveness of monoclonal antibodies that have shown activity against relapsed HL.This article is available for continuing medical education credit at CME.TheOncologist.com. CME CME ABSTRACTHodgkin's lymphoma (HL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 61 publications
0
21
0
1
Order By: Relevance
“…2,20 For methodological reasons, it is impossible to compare response rate among these regimens. It is the recommendation of the LYSA expert panel to use a platinum-based regimen such as DHAP (dexamethasone, high-dose cytarabine-cisplatin) or ICE (ifosfamide-carboplatin-etoposide) for patients previously treated with ABVD or BEACOPP (especially if mediastinal radiotherapy has been delivered), given the risk of cardiac toxicity if the cumulative dose of doxorubicin has already reached 300-400 mg/m 2 .…”
Section: Second-line Regimensmentioning
confidence: 99%
See 1 more Smart Citation
“…2,20 For methodological reasons, it is impossible to compare response rate among these regimens. It is the recommendation of the LYSA expert panel to use a platinum-based regimen such as DHAP (dexamethasone, high-dose cytarabine-cisplatin) or ICE (ifosfamide-carboplatin-etoposide) for patients previously treated with ABVD or BEACOPP (especially if mediastinal radiotherapy has been delivered), given the risk of cardiac toxicity if the cumulative dose of doxorubicin has already reached 300-400 mg/m 2 .…”
Section: Second-line Regimensmentioning
confidence: 99%
“…Some experts suggested that this strategy should also be proposed to patients accumulating poor-risk factors, as well as in patients needing more than one line of salvage chemotherapy before displaying chemosensitivity, in agreement with the recommendations of Mendler and Friedberg. 20 In contrast, other LYSA experts emphasize that this latter group of patients are at high risk for rapid progression before any GVL effect can occur, and that they should then be oriented toward a second ASCT rather than RIC-allo. Benefit to risk ratio of RIC-allo and donor availability should also be weighted in the decision.…”
Section: Allogeneic Stem-cell Transplantationmentioning
confidence: 99%
“…Currently, in such cases the standard procedure is to implement a phase II rescue chemotherapy and mega-dose chemotherapy supported by autologous haematopoietic stem cell transplantation [9]. In the described case, such a treatment was chosen; however, due to the failure of stem cell collection, it was decided to conduct an allogeneic transplantation from a related donor: in this case, a brother.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the introduction of reduced intensity conditioning (RIC) allowed a reduction in transplant related mortality. Analysis of the data demonstrate that RIC with alloHSCT enables long survival in 20-30% of patients [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Оче-видным является и то, что возможность достижения ремиссии зависит от противоопухолевой эффективно-сти выбранного индукционного режима [63,64]. Од-нако к понятию «эффективность» индукционного режима у больных, которым планируется проведение ТКПГ, предъявляется гораздо больше требований, чем просто высокая частота достижения ремиссий.…”
Section: роль индукционной терапииunclassified